IS A CONFEDERATION BETWEEN ISRAEL AND PALESTINE WITH JORDAN A VIABLE ARRANGEMENT?. (December 2022) - Bar-Tal, Daniel
The present article considers the viability of a confederation between Israel and the Palestinian Authority with Jordan as a realistic solution to the ongoing conflict between Israeli Jews and Palestinians. It presents the background and the course of the Israeli–Palestinian conflict, with a description of the present situation in order to understand the possible solutions to the conflict. I also explore several ideas of how to peacefully resolve the conflict that is entertained at present. A special focus is on the proposal of Alon Ben-Meir (2022) about building a confederation delineated in the Spring issue of this journal. Thus, in the second part, the concept of confederation is described and three barriers to its implementation are elaborated. The first discusses the approach of presenting a rational plan, whereas in reality, participants in conflict develop a sociopsychological repertoire that serves often as a barrier to the solution. The second comment elaborates on the complex nature of reconciliation that cannot be required as a necessary precondition for the solution of the conflict. The third comment pertains to the asymmetry of the parties in the Israeli–Palestinian conflict that is a serious barrier to the implementation of the phases of the proposed confederation. Finally, I describe briefly the different proposals that are on the table at present and evaluate their feasibility.